Peningkatan Hasil Belajar dan Kolaborasi Menggunakan Model Problem Based Learning (PBL) Berbantuan Audio Visual pada Materi Peran Keluarga Bagi Perkembanganku Fase D Kelas VII di SMP Negeri 2 Sunggal - Dwinata Purba; Yusmanto Yusmanto; Busri Busri (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research is aimed to improve the teaching learning process and learning outcomes of Catholic Religious Education and Characters through the Problem Based Learning model. This research is Classroom Action Research. The subjects of the research were the tenth students of the seventh grade of SMP Negeri 2 Sunggal academic year of 2024/2025. The data analysis technique is descriptive analysis consisting of students’ affective learning outcomes data and students’ cognitive learning outcomes data through observation and written tests. The research was conducted in two cycles. The result of the research shows that the percentage of the students’ completeness has increased in each cylce which is 60% to 80%, and the degree of students’ participation in the learning process has increased from 50% to 80%. It can be concluded that the Problem Based Learning model improves the learning outcomes in Catholic Religious Education and Characters of the seventh grade students in SMP Negeri 2 Sunggal in the topic of The family’s role for my selfgrowth and The Friend’s role for my selfgrowth”.